2014
DOI: 10.1002/2013gc004983
|View full text |Cite
|
Sign up to set email alerts
|

Model evaluation of the coherence of a common source water oxygen isotopic signal recorded by tree-ring cellulose and speleothem calcite

Abstract: O records of the two proxies. When the former is higher than or comparable with the latter, finding one to one correspondence between the d 18 O records of the two proxies could be challenging. Modeling exercise revealed a favorable climatic condition at Jagdalpur (19.08 N, 82.03 E), a potential tropical location for tree ring and speleothem-based climate reconstruction, for inheriting a common source water d 18 O signal in both the proxies. d 18 O records of tree ring and annually resolved speleothem from Jag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 73 publications
(139 reference statements)
0
5
0
Order By: Relevance
“…However, comparable mechanistic insight into what determines variability in the isotope composition of a plant's source water does not exist. The approximation of a plant's source water d 2 H and d 18 O from precipitation isotope databases, such as the Global Network of Isotopes in Precipitation (GNIP) database (Kanner et al, 2013;Managave, 2014;Dee et al, 2015), or derived products, such as the Online Isotope Calculator for Precipitation (OIPC) (Bowen & Wilkinson, 2002;Richter et al, 2008), is therefore still difficult and can introduce large uncertainties, for example in the interpretation of H and O isotopes in tree ring records and leaf wax lipids.…”
Section: Introductionmentioning
confidence: 99%
“…However, comparable mechanistic insight into what determines variability in the isotope composition of a plant's source water does not exist. The approximation of a plant's source water d 2 H and d 18 O from precipitation isotope databases, such as the Global Network of Isotopes in Precipitation (GNIP) database (Kanner et al, 2013;Managave, 2014;Dee et al, 2015), or derived products, such as the Online Isotope Calculator for Precipitation (OIPC) (Bowen & Wilkinson, 2002;Richter et al, 2008), is therefore still difficult and can introduce large uncertainties, for example in the interpretation of H and O isotopes in tree ring records and leaf wax lipids.…”
Section: Introductionmentioning
confidence: 99%
“…The values of 𝑒 𝑖 were estimated from the leaf temperature. Boundary layer conductance was considered as 1 mol m -2 s -1 (Roden et al, 1999;Managave et al, 2014). Tipple et al, (2015) showed the utility of the Craig-Gordon model in modeling δD values of n-alkanes.…”
Section: Leaf Wax N-alkanes and N-alkanoic Acidsmentioning
confidence: 99%
“…The isotopic composition of the leaf water calculated using Equation 1 is sensitive mainly to (i) leaf temperature, (ii) relative humidity, (iii) isotopic composition of the xylem water (i.e. source water) and atmospheric water vapor (Sachse et al, 2009;Managave, 2014).…”
Section: Leaf Wax N-alkanes and N-alkanoic Acidsmentioning
confidence: 99%
“…The subfossil samples found in the caves (Figure S16) radiocarbon ( 14 C) dates were wiggle matched against the Southern Hemisphere calibration curve [59][60] , and indicated an overlap of two A. cearensis during the Little Ice Age (LIA) . Then, synchronization of this tree-ring δ 18 O floating record with local speleothem δ 18 O series, that share a common source water δ 18 O signal 41 and have similar inter-annual and decadal variability in the recent decades (Figure S12, and S19), pointed out a position of significant correlation between records from 1527 to 1690 (r = 0.34 p < 0.01, Figure S19). During this period, and similar to recent years, climate model simulations for the site (CESM-LME) show a temperature increase (Figure 6A), a decrease in relative humidity (Figure 6B) and small decrease in precipitation (Figure 6C).…”
Section: Effects Of Vpd In a Broader Temporal Contextmentioning
confidence: 92%
“…Tree-ring widht and growth are intimately coupled to regional climate 37,38 . Local and global climate can also affect the stable oxygen isotope ratios (δ 18 O) in tree rings, offering an additional proxy to improving cross-dating, understanding tree physiological responses, enhancing climate signal intensity, spatial coverage [39][40] , and enabling comparison with other archives 41 . Trees absorb water from rainfall with an δ 18 O signal determined by the temperature of condensation, which have little variation in tropical lowlands, and the amount of rainfall, both local or upstream 42 .…”
Section: Introductionmentioning
confidence: 99%